2008
DOI: 10.1061/(asce)0887-3801(2008)22:3(216)
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Municipal Infrastructure Asset Management Processes: Challenges and Solutions

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(41 citation statements)
references
References 12 publications
0
40
0
1
Order By: Relevance
“…Diğer yandan, varlıkların durumlarının değerlendirilmesi ve değer biçme işlemlerinde standart bir kılavuzun bulunmaması da bir zorluktur. Buna ek olarak; denetleme yöntemleri, yüksek işçi maliyetleri nedeniyle masraflıdır ve yapısal denetleme yöntemlerinin çoğu tahrip edici işlemlerdir [7]. Kalifiye mühendislerin yetersiz olması nedeniyle varlık yönetimi sisteminin karmaşıklığını azaltmak amacıyla yazılımlar geliştirilmesine rağmen, varlık yönetimi yazılımları tam kapasiteyle kullanılamamaktadır [8].…”
Section: Varlik Yöneti̇mi̇nde Faydalar Ve Zorluklarunclassified
“…Diğer yandan, varlıkların durumlarının değerlendirilmesi ve değer biçme işlemlerinde standart bir kılavuzun bulunmaması da bir zorluktur. Buna ek olarak; denetleme yöntemleri, yüksek işçi maliyetleri nedeniyle masraflıdır ve yapısal denetleme yöntemlerinin çoğu tahrip edici işlemlerdir [7]. Kalifiye mühendislerin yetersiz olması nedeniyle varlık yönetimi sisteminin karmaşıklığını azaltmak amacıyla yazılımlar geliştirilmesine rağmen, varlık yönetimi yazılımları tam kapasiteyle kullanılamamaktadır [8].…”
Section: Varlik Yöneti̇mi̇nde Faydalar Ve Zorluklarunclassified
“…As a result, this research focused on the following research question: what are the barriers that infrastructure organizations face when establishing and implementing an asset management system and how do they vary between developing and developed economies? Poister et al 2013;Shiferaw et al 2002;FHWA 2007;Schraven et al 2011 Lack of identified processes and control procedures (e.g., no consideration for budgets scenarios; no criteria to optimize use of funds; undefined repairs' strategies) Mizusawa and McNeil 2006;McNeil et al 2000;Hassanain et al 2003;Halfawy, 2008;Arif and Bayraktar 2012 Inconsistent decisions by the decision makers (e.g., the organization decides to build a wastewater treatment plant without taking into account a project to connect the network's pipes) Grussing 2014;Shiferaw et al 2002;FHWA, 2007;Schraven et al 2011;Arif and Bayraktar 2012;Vanier 2001;Flyvbjerg 2007 Managerial/ Organizational: Lack of top management support (e.g., no action decisions are taken about any management system development; no long term support of management plans; no implementation of planned criteria) Brunetto et al 2014;Lizarralde et al 2013;Mizusawa and McNeil 2006;Cooksey et al 2011 Lack of communication channels within organizations and departments (e.g., different departments do not share their plans to create a general plan for the organization) FHWA 2007; Brunetto et al 2014;Cooksey et al 2011;Lizarralde et al 2013;Vanier 2001;Yankov and Kleiner 2001 Lack of scope and job description within the organization/ agency (e.g., there is no clear identification of the responsibilities and authorities for managers in different levels in the organization) Atkinson et al 2006;Arts and Van Lamoen 2005;Ziara et al 2002;PMI 2013 Lack of performance monitoring (e.g., no clear criteria; no announced indicators; unclear procedures) Cooksey et al 2011;…”
Section: Literature Review On Potential Asset Management Barriersmentioning
confidence: 99%
“…Infrastructure performance models are not specific to local conditions (e.g., organization uses performance prediction models with no consideration to the local conditions such as number of users and local environment; these conditions could be different from the original assumptions of the model) Cooksey et al 2011;Vanier 2001;Halfawy 2008;RepCard 2013;Uddin et al 2013;Grussing 2014 Using an incompatible technology with local conditions (e.g., very sophisticated systems, which are not compatible with other procedures) Using an incompatible operational process with local conditions (e.g., asking for specific data, which the operators do not have the tools to determine) Shiferaw, 2002;Bakuli, 1994;Wall 1993;Sohail et al 2002;Javernick-Will & Scott 2010 Lack of regulations to enhance accountability (e.g., there are no regulations that force organizations to use a clear criteria in making their decisions, such as cost-effectiveness, to select among candidate projects) Sohail and Cavill 2008;Wooldridge et al 2001;Burns et al 1999;Benito et al 2008;Acerete et al 2009 Lack of trust between different organizations and departments (e.g., departments do not provide reliable information about their performance between each other, departments change data in the regular reports and meetings to be in good shape) Ika et al 2012;Burns et al 1999 Prevalence of corruption (e.g., at the government level, consulting level) Sohail and Cavill 2008;Kenny 2009;Nordin et al 2011;Golden and Picci 2006;Bowen et al 2012 Undefined contracting criteria (e.g., undefined processes for contracting type (delivery method) selection; undefined contract documents for different type of contracts; undefined procedures for contractors' selection) Mollaoglu-Korkmaz et al 2013, Kumarasawy et al 2005, Garvin 2010 Centralized decision-making (e.g., no permission for the branches to make any decisions; everything is done in the main office) Lizarralde et al 2013, FHWA 2007 Political participation interfering with projects' decisi...…”
Section: Local Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…RE managers have already acknowledged the benefit of professional RE management as it enables not only to reduce the costs, but also helps to solve social and developmental issues as well as those concerning expansion of the cities (Halfawy 2008).…”
Section: Introductionmentioning
confidence: 99%